In situ starch and crude protein degradation in the rumen and in vitro gas production kinetics of wheat genotypes1. Issue 4 (9th June 2016) - Seifried, N.; Steingass, H.; Hoffmann, N.; Rodehutscord, M.
Summary: The objective of this study was to determine the variation of in situ ruminal degradation characteristics of dry matter (DM), crude protein (CP) and starch (ST), and to determine the effective degradation (ED) of wheat genotypes. Further, multivariate associations of these in situ values with their corresponding in vitro gas production (GP) kinetics and laboratory measurements were evaluated using correlation and multiple linear regression analyses. Grains of 20 genotypes of wheat were characterized by proximate constituents, amino acid (AA) composition and physical characteristics. Ruminal degradation kinetics were determined by in situ degradation of DM, CP and ST, and subsequent evaluation of in vitro GP relative to time courses. In situ and GP measurements were fitted to an exponential equation, and ED was calculated using passage rates in the rumen of 5%/h (ED5) and 8%/h (ED8). To predict ED8 of CP (EDCP8) and ST (EDST8), correlations were evaluated and stepwise multiple linear regression analyses were applied. Estimated degradation parameters varied considerably between wheat genotypes irrespective of the nutrient tested. Variance in a, b and c was not reflected in the variation of the ED, due to high degradation rates ( c ). The assumed passage rate also impacted estimation of the ED minimally. Estimated GP parameters varied only slightly among wheat genotypes. Nevertheless, regression models explained up to 80 and 99% of the variance in EDCP8 and EDST8, respectively, and associations between EDST8 and EDCP8 and chemical and physical characteristics of grains were detected. As ST is the primary nutrient in wheat grains and can comprise substantial portions of dairy rations, the total amount of ST as well as its ED in the rumen should be taken into account when wheat is incorporated into dairy rations. Conversely, variance in wheat grain CP degradation was very low and can largely be neglected in practical ration formulation for ruminants.